Millennials Interest in Fabric Masks in Covid-19 Era - Marniati, Marniati; Lutfiati, Dewi; Puspitorini, Arita; Mayasari, Peppy (International Journal for Educational and Vocational Studies, 2020)
This study aims to measure the interest of a group of young people in the use of fabric masks in the Covid-19 era in terms of the value of needs, designs, colors, types of materials, and accessories. This study uses a quantitative approach. The research subjects were all new students of 2020, the Department of Home Economics Education with a sample of 228. The data collection method used a questionnaire with a Likert scale model of four alternative answers. The data analysis technique used descriptive analysis of the frequency distribution and exploratory factor analysis. The instrument validity was proven by Product Moment Correlation, while its reliability was tested by Cronbach’s Alpha. The results showed that the mask design was more explained by colors, materials, and fashionable factors, while mask values were due to consideration of needs and protection factors